2000
DOI: 10.1016/s0022-5347(05)67199-6
|View full text |Cite
|
Sign up to set email alerts
|

The Morphological, in Situ Effects of a Self-Reinforced Bioabsorbable Polylactide (Sr-Pla 96) Ureteric Stent; An Experimental Study

Abstract: SR-PLA 96 spiral stent is regarded highly compatible and SR-PLA 96 might be a suitable material for a partial ureteric stent. Biodegradation of a SR-PLA 96 stent makes stent removal unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In addition to pain, indwelling stents stimulate and irritate the bladder mucous membrane, resulting in a wide range of urinary symptoms including dysuria, urgency, hematuria and UTI. Experiments showed that long-indwelling stents cause ureteral wall edema, epithelial hyperplasia, destruction, and inflammatory cell reactions, suggesting their use only over the short term [42]. Usually 4 weeks after stent implantation, late complications appear such as hydronephrosis, stent migration, encrustation, fragmentation and breakage [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pain, indwelling stents stimulate and irritate the bladder mucous membrane, resulting in a wide range of urinary symptoms including dysuria, urgency, hematuria and UTI. Experiments showed that long-indwelling stents cause ureteral wall edema, epithelial hyperplasia, destruction, and inflammatory cell reactions, suggesting their use only over the short term [42]. Usually 4 weeks after stent implantation, late complications appear such as hydronephrosis, stent migration, encrustation, fragmentation and breakage [43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models have revealed biological reactions to stent insertion in the form of epithelial destruction with erosions, ulcerations of the transitional epithelium, and inflammatory reactive changes within 6 weeks of stenting the animals' ureter [3134]. Thus, the mechanical trauma associated with stent placement may injure the uroepithelium, allowing for latent BK virus to enter replicative phases.…”
Section: Discussionmentioning
confidence: 99%
“…Routine stent placement has been questioned for a long time, especially in relation to balloon dilatation and ureteroscopy for urolithiasis ( 18 ). The use of a stent is recommended only for the short period required to prevent the obstruction and renal failure due to edema, epithelial hyperplasia, or inflammatory cell reaction ( 19 ). Moreover, some authors have recently suggested that the ureteral stent is not necessary in uncomplicated procedures ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%